Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) ĐKXĐ: x - 2 \(\ne\)0 x \(\ne\)2
x + 2 \(\ne\)0 => x\(\ne\)-2 =>x \(\ne\)\(\pm\)2 và x \(\ne\)-10
x2 - 4 \(\ne\)0 x \(\ne\)\(\pm\)2
x + 10 \(\ne\)0 x \(\ne\)-10
b) Ta có: P = \(\left(\frac{x+5}{x-2}+\frac{3x}{x+2}-\frac{4x^2}{x^2-4}\right)\cdot\frac{x^2+2x}{x+10}\)
P = \(\left(\frac{\left(x+5\right)\left(x+2\right)}{\left(x-2\right)\left(x+2\right)}+\frac{3x\left(x-2\right)}{\left(x+2\right)\left(x-2\right)}-\frac{4x^2}{\left(x-2\right)\left(x+2\right)}\right)\cdot\frac{x\left(x+2\right)}{x+10}\)
P = \(\left(\frac{x^2+2x+5x+10+3x^2-6x-4x^2}{\left(x-2\right)\left(x+2\right)}\right)\cdot\frac{x\left(x+2\right)}{x+10}\)
P = \(\frac{x+10}{\left(x-2\right)\left(x+2\right)}\cdot\frac{x\left(x+2\right)}{x+10}\)
P = \(\frac{x}{x-2}\)
c)Với x \(\ne\)\(\pm\)2 và x \(\ne\)-10
Ta có: x2 - x - 6 = 0
=> x2 - 3x + 2x - 6 = 0
=> x(x - 3) + 2(x - 3) = 0
=> (x + 2)(x- 3) = 0
=> \(\orbr{\begin{cases}x+2=0\\x-3=0\end{cases}}\)
=> \(\orbr{\begin{cases}x=-2\left(ktm\right)\\x=3\end{cases}}\)
Với x = 3 => P = \(\frac{3}{3-2}=3\)
a) x2 - 5x - y2 -5y
= ( x2 - y2 ) + ( -5x - 5y)
= ( x - y ) ( x + y) - 5( x + y )
= ( x + y ) ( x - y -5)
b) x3 + 2x2 - 4x - 8
= x2 ( x + 2 ) - 4 ( x + 2 )
= ( x +2 ) ( x2 -4 )
= ( x+2)2 ( x-2)
Bai 2 :
a, \(A=\left(x+3\right)^2+\left(x-2\right)^2-2\left(x+3\right)\left(x-2\right)\)
\(=x^2+6x+9+x^2-4x+4-2\left(x^2-2x+3x-6\right)\)
\(=2x^2+2x+13-2x^2-2x+12=25\)
b, \(B=\left(x-2\right)^2-x\left(x-1\right)\left(x-3\right)+3x^2-9x+8\)
\(=x^2-4x+4-x\left(x^2-3x-x+3\right)+3x^2-9x+8\)
\(=4x^2-13x+12-x^3+4x^2-3x=-16x+12-x^3\)
a) Mình không hiểu đề cho lắm
b) \(3x\left(x-1\right)^2-2x\left(x+3\right)\left(x-3\right)+4x\left(x-4\right)\)
\(=3x\left(x^2-2x+1\right)-2x\left(x^2-9\right)+4x\left(x-4\right)\)
\(=3x^3-6x^2+3x-2x^3+18x+4x^2-16x\)
\(=x^3-2x^2+5x\)
c) \(2\left(2x+5\right)^2-3\left(4x+1\right)\left(1-4x\right)\)
\(=2\left(2x+5\right)^2+3\left(4x+1\right)\left(4x-1\right)\)
\(=2\left(4x^2+20x+25\right)+3\left(16x^2-1\right)\)
\(=8x^2+40x+50+48x^2-3\)
\(=56x^2+40x+47\)
d) \(x\left(x+4\right)\left(x-4\right)-\left(x^2+1\right)\left(x^2-1\right)\)
\(=x\left(x^2-16\right)-\left(x^4-1\right)\)
\(=x^3-16x-x^4+1\)
e) \(\left(y-3\right)\left(y+3\right)\left(y^2+9\right)-\left(y^2+2\right)\left(y^2-2\right)\)
\(=\left(y^2-9\right)\left(y^2+9\right)-\left(y^4-4\right)\)
\(=y^4-81-y^4+4\)
\(=-77\)